The emerging technology of big data : its impact as a tool of ICT development - Susanto, Heru, 1965-; Fang-Yie, Leu; Chen, Chin Kang (Toronto ; New Jersey : Apple Academic Press, 2019)
'Big Data is now highly regarded and accepted as a useful tool to help organizations manage their data and information effectively and efficiently. This new volume, The Emerging Technology of Big Data: Its Impact as a Tool of ICT Development, looks at the new technology that has emerged to meet the growing need and demand and studies the impact of Big Data in several areas of today's society, including social media, business process re-engineering, science, e-learning, higher education, business intelligence, and green computing. In today's modern society, information system (IS) through Big Data contributes to the success of organizations because it provides a solid foundation for increasing both efficiency and productivity. Many business organizations and educational institutions realize that compliance with Big Data will affect their prospects for success. Everyday, the amount of data collected from digital tools grows tremendously. As the amount of data increases, the use of IS becomes more and more essential. The book also looks at how large datasets and analytics have slowly crept into the world of education and discusses methods of teaching and learning and the collection of student-learning data'--
Managing big data's impact on social media for organization business process reengineering / Heru Susanto -- Is it possible to conduct education processes using big data? Challenges and opportunity / Heru Susanto -- Revealing the big data revolution as a driver of science achievement in today's globalization / Heru Susanto and Leu Fang-Yie -- Toward big data's impact on the learning process : Generation Y and Z perspectives / Heru Susanto -- Creating technopreneurs and innovation : a big data approach / Heru Susanto and Chin Kang Chen -- Enabling online education : an academic aspect / Heru Susanto, Leu Fang-Yie, and Chin Kang Chen -- The evolution of learning analytics through big data's emerging technology / Heru Susanto and Chin Kang Chen -- Business intelligence and analytics : a Big Data paradigm / Heru Susanto -- Crafting strategies through ICT as an enabler of business process reengineering / Heru Susanto -- Managing online learning : big data, social networks, and cloud computing / Chin Kang Chen, Heru Susanto, and Leu Fang-Yie -- Green information and communication technology awareness as a corporate strategy for information systems / Heru Susanto, Leu Fang-Yie, and Chin Kang Chen.
Includes bibliographical references and index.
Keywords: Big data; Information technology